PENERAPAN BIRTH BALL PADA IBU BERSALIN - Anggraeni, Rina Dwi; Suryani, Eka (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
An abnormally timed delivery due to prolonged labor. Factors that affect the length of labor are presentation abnormalities, inadequate contractions, birth canal abnormalities, multiple pregnancies, and anemia. To prevent prolonged labor, there are several ways, namely yoga, pregnancy exercise and birthball techniques. During pregnancy, pregnant women can use a birthing ball when the gestational age enters the third trimester. At this gestational age, the growing size of the fetus can put pressure on the blood vessels and nerves in the pelvic and back area. This often makes pregnant women feel pain in the area. Birthing balls can be used by pregnant women to replace ordinary chairs and to exercise. Sitting with a birthing ball in the third trimester of pregnancy can be more comfortable for pregnant women. This ball also makes it easier for pregnant women to get up to stand